(untitled) (Itinera, 2013)
Against Cartesian dualism and in line with the general twentieth-century rediscovery of body and perception, this paper aims to examine the role of senses for the performer, as presented by Richard Schechner’s theory of performance. Such a theory finds its legitimacy in the pages of the philosopher Mearleu-Ponty, and in the priority the philosopher assigned to perception and senses as sources of knowledge, as well as opening of consciousness to the world.